2018
DOI: 10.1016/j.cmi.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Four-year safety follow-up of the tetravalent dengue vaccine efficacy randomized controlled trials in Asia and Latin America

Abstract: The overall benefit-risk remained positive in those aged ≥9 years up to year 4, although the protective effect was lower in years 3 and 4 than in years 1 and 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 13 publications
1
43
0
2
Order By: Relevance
“…Indeed, the underperformance of Dengvaxia (9-14), a tetravalent DENV vaccine with the prM and E proteins of DENV and the backbone of yellow fever virus, illustrates the possible danger of a vaccine that primarily targets the generation of neutralizing antibodies, but not antiviral T cells. Not only has Dengvaxia failed to fully protect against DENV infection, it increases the risk of hospitalization in DENV-naïve individuals when compared to unvaccinated individuals (9,15,16). One possible advantage of a live-attenuated vaccine like DLAV is that it induces balanced CD8 + and CD4 + T cells responses to all four DENV serotypes after a single dose, with a particular focus on several of the DENV non-structural proteins that are missing from Dengvaxia (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the underperformance of Dengvaxia (9-14), a tetravalent DENV vaccine with the prM and E proteins of DENV and the backbone of yellow fever virus, illustrates the possible danger of a vaccine that primarily targets the generation of neutralizing antibodies, but not antiviral T cells. Not only has Dengvaxia failed to fully protect against DENV infection, it increases the risk of hospitalization in DENV-naïve individuals when compared to unvaccinated individuals (9,15,16). One possible advantage of a live-attenuated vaccine like DLAV is that it induces balanced CD8 + and CD4 + T cells responses to all four DENV serotypes after a single dose, with a particular focus on several of the DENV non-structural proteins that are missing from Dengvaxia (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of Dengvaxia R in humans and non-human primates suggested incomplete immunity (10) and imbalanced antibody responses across serotypes in early human trials (11)(12)(13)(14). Field data now confirms that individuals who are dengue-naïve when they received Dengvaxia R have a higher risk of hospitalization with subsequent dengue infection compared with unvaccinated individuals (9,15,16). A possible contributing mechanism to poor protection may be the vaccine's lack of nonstructural DENV proteins, which have been demonstrated to be the predominant target of dengue-specific CD4 + and CD8 + T cell responses (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 92%
“…At the 4‐year follow‐up, the trend of higher risk in the < 9 years age group, while less pronounced compared with the 3‐year follow‐up, was still present. In the immunogenicity subgroups which captured pre‐vaccination status of a small proportion of the study participants (7.5–20%, depending on the trial), a higher risk of hospitalised virologically confirmed dengue was apparent for seronegative vaccine recipients . Experts in the field raised concerns about the broader use of the vaccine in young children in endemic countries and highlighted the need for further examination of the role of age and pre‐vaccination serostatus with CYD‐TDV vaccination …”
mentioning
confidence: 99%
“…In the immunogenicity subgroups which captured prevaccination status of a small proportion of the study participants (7.5-20%, depending on the trial), a higher risk of hospitalised virologically confirmed dengue was apparent for seronegative vaccine recipients. 7 Experts in the field raised concerns about the broader use of the vaccine in young children in endemic 1 Current Strategic Advisory Group of Experts on Immunization recommendations 3…”
mentioning
confidence: 99%
“…Therefore, the a priori planned long-term follow-up to 6 years of the first licensed tetravalent dengue vaccine, CYD-TDV (Dengvaxia ® ), developed by Sanofi Pasteur, is to be commended. This month's issue in Clinical Microbiology and Infection provides important interim 4-year follow-up data on the protection and safety of CYD-TDV [8].…”
mentioning
confidence: 99%